Government policies and business strategies towards an innovative and competitive economy - Jansze, Wim (2007)
Proposes a hybrid path for Suriname in which the technological innovation of firms and the policies of government need to be strengthened. Opines that this path can only be adopted if on the one hand government changes its politics, technology policy and focus, and on the other hand the innovative nature of companies is enchanced. Suggests that the outlook over the hybrid path views a service-based strategy by government combined with a focus strategy of firms.